Fatigue Assessment of Existing Bridge Members - Vican, Josef; Gocal, Jozef; Melis, Branislav (Communications - Scientific letters of the University of Zilina, 2007)
Correct consideration of the service load effects plays a very important role on assessment of railway bridges, especially on fatigue assessment. Eurocode EN 1991-2 introduces twelve types of service trains and prescribes their sequel in normal and heavy duty. The service trains, consisting of locomotive and defined number of wagons, are specified by amount of axle forces and distances between them. However, there is no commentary which would illuminate a background of the service trains technical data. Consequently, it is difficult to say how representative the service load models specified in this standard prescription are in comparison with the actual railway traffic effects, namely in conditions of the Slovak Railways. Therefore, the paper deals with confrontation of the actual railway traffic load effects and the effects of traffic load defined in EN 1991-2. The confrontation is based on fatigue assessment of existing railway bridge truss girder.